PENGARUH PELATIHAN DAN PENGEMBANGAN SUMBER DAYA INSANI TERHADAP ETOS KERJA KARYAWAN BANK JABAR BANTEN (BJB) SYARIAH KCP CIAMIS - Tiara Ramadanti (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2019)
This research was conducted to determine the effect of training on the work ethic of employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis, as well as the influence of human resource development on the work ethic of employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis, and to determine the training and human resource development. simultaneous influence on the work ethic of employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis. This research uses quantitative research methods. The data collection technique is done by filling out questionnaires, observing and interviewing. This research uses non probability sampling with saturated sampling technique. This is because the population is relatively small, namely only 14 employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis. The analysis model used is descriptive analysis, validity test, reliability test, classic assumption test, multiple linear regression analysis and hypothesis testing with a significance level of 5% or 0.05, then in this study, the author uses the SPSS 20 application to process the data. This study shows that partially training has a significant effect on the work ethic of employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis as evidenced by the value of tcount> ttable of 5.428> 2.20099 and the human resource development variable partially has a significant effect on the work ethic of Bank Jabar employees. Banten (BJB) Syariah KCP Ciamis is proven by the value of tcount> ttable of 6,000> 2,20099. Meanwhile, the training and human resource development variables simultaneously affect the work ethic of the employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis as evidenced by Fcount> Ftable of 288.792> 3.89. Then the results of the contribution of the coefficient of determination (R2 test) show that training and human resource development have an influence on the work ethic of employees of Bank Jabar Banten (BJB) Syariah KCP Ciamis by 97.8%. The remaining 2.2% is influenced by other unknown variables and is not included in this study